SELF-ARCHIVING AND OPEN ACCESS: digital rights and duties in the network society - Ferrari, Rodrigo Duarte Duarte (2014)
This article presents an investigation into the self-archiving in digital repositories as a relationship of rights and duties in the context of the network society and open access. We start with a case study on the perception of Brazilian researchers about the uses and purposes of the Institutional Repository of CEDES Network. This created conditions to observe and reflect on the social and political commitment of the researchers of CEDES Network to organize and make available their products of that ministerial action in open access. We conducted ten interviews with researchers of CEDES Network in the period of 19/11/2010 to 14/09/2011 and used some statistics of the RIRC and the network itself as data. In this text, we present a discussion about self-archiving in RIRC from three main concepts: collective distribution; collective intelligence; participative culture. As a result of this research, we found that there are contradictions between discourse guided by the ideal qualities of digital repositories and open access in contrast to the effective practice that should materialize this discourse.